The Role of the Computerized Music Program Sibelius Version 7 (7 Sibelius) and Its Support for Students Playing Arabic Musical Instruments: An Applied Study - Al-Mallah, Mohammad Ali Reda; Haddad, Abdel Salam Marei (Dirasat: Human and Social Sciences, 2025)
Objectives: This study explores the impact of music programs on Arab musical creativity, particularly among students who play musical instruments, aiming to raise awareness about technology’s role in education. The study aims to demonstrate the importance of music programs for students and their contribution to problem-solving, assistance, and the enhancement of technical knowledge. It also aims to present the concept of technology and its impact on performance disciplines. Methods: Employing an applied descriptive approach, drawing on performance experience and university teaching, the study follows musicians who have studied both music and computers. The study emphasizes the importance of computerized programs and provides a historical summary of audio-visual technological development stages, demonstrating students’ creativity stages. Positive results were observed in musical performance strength and the use of the Sibelius program. Results: The study highlights the importance of modern educational and technological means, especially the Sibelius program, in serving Arabic musical instrument players for playing, recording, and transcribing music pieces. The study reached several recommendations, the most important of which is the necessity to intensify the teaching of music programs and integrate them into music education curricula. Conclusions: The study concludes by defining the importance of music programs, their utilization, and their role in enhancing skills in teaching Arabic musical instruments. It presents the benefits of the program, such as arrangement harmony and extracting melodic phrases. The smoothness of dealing with programs in terms of speed and memorization is emphasized, along with the importance of instrument inclusion in modern programs.